Linguistic Indicators for Text Complexity in Picture Books for Young Chinese Children Learning English as a Foreign Language - Zhao, Jing; Zhu, Meifang; de Ruiter, Laura; Chen, Si (Frontiers in Education, 2022)
We examined the linguistic features of texts in twenty-nine picture books used in an early English as a Foreign Language program in China. We used the software CLAN to automatically extract indices of linguistic complexity that are typically used to analyze child-directed speech and tested if these indices aligned with expert judgments on the books’ appropriate grade level (Kindergarten-1 through Kindergarten-3). Of the eleven characteristics investigated, seven showed significant between-level differences with moderate effect sizes. Across all levels, vocabulary complexity (i.e., frequency of types, frequency of tokens, and vocabulary diversity) and syntactic complexity (i.e., number of verbs per utterance, number of Developmental-Sentence-Scoring-eligible utterances, mean length of utterance in morphemes, and total number of non-zero morphemes) increased, also in alignment with experts’ judgments. Indices of child language development can thus be used to estimate text complexity in picture books. The study contributes to a better understanding of children’s picture book difficulty and has methodological implications for investigating text characteristics for very young children learning English as a foreign language.